Safety and effectiveness of apixaban use for stroke prevention during Ramadan fasting (the API-RAM study) - Ghrab, Aiman; Gargouri, Rania; Addad, Faouzi; Cheikhrouhou, Anis; Jabeur, Mariem; Charfeddine, Selma; Bahloul, Amine; Triki, Zied; Ellouze, Tarek; Abidi, Omar; Mallek, Souad; Triki, Faten; et al. (Frontiers in Pharmacology, 2025)
IntroductionPatients receiving anticoagulation for atrial fibrillation (AF) are required to consult their doctor before starting Ramadan fasting to get their authorization for fasting and adapt their treatment. More often, a once-daily regimen is proposed to facilitate their intake schedule. Apixaban, a direct oral anticoagulant, prescribed twice daily with an optimal benefit/risk ratio in numerous situations, has very limited data regarding its use during Ramadan.AimThe aim of this study was to evaluate the safety and the efficacy of apixaban for stroke prevention in AF patients during the month of Ramadan.MethodsAn observational, multicentric study was performed in Tunisia during two consecutive years during the specific month of Ramadan. The API-RAM study included AF patients who were on apixaban and fasted at least 10 days. Efficacy was defined by the absence of ischemic events, and safety was established by classifying bleeding events using the BARC (Bleeding Academic Research Consortium) classification during the study period.ResultsA total of 257 patients were included in our study. No ischemic events were reported during the study period. Minor bleeding events were reported in only 12 patients (4.7%), with no major bleeding event. Based on multivariate analysis, independent predictors for the bleeding risk of our population were as follows: smoking, history of hypertension, and creatinine clearance.ConclusionApixaban seems to be safe and effective for the prevention of the thromboembolic episode in AF patients during Ramadan fasting. Larger studies such as randomized clinical trials are necessary to confirm these results.